(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: Outbreaks of tuberculosis and drug-resistant tuberculosis are the main threat to tuberculosis control globally. Drug adherence in patients with drug-resistant tuberculosis needs to be investigated and interventions to improve the effectiveness of treatment for patients. Objectives: Describing the status of drug adherence among drug-resistant TB patients at Hanoi Lung Hospital and some related factors in 2018. Methods: Cross-sectional survey. Results and conclusion: The rate of patient’s adherence to medication use in the attack phase was 51,1%, in the maintenance phase was 54,8% and in overall adherence rate was 53,1%. The factors associated with statistical significance with adherence to drugs for drug-resistant TB include: Factors belonging to the patients (education level, knowledge of drug-resistant TB, comorbidities, risk behavior risks such as drinking beer/alcohol, smoking tobacco/waterpipe and drugs use), family and social factors, health service factors and drugs/treatment regimens (p<0.05).